Digital Twin in Tourism and National Park Management: A Bibliometric Analysis from an Information Systems Perspective - Aditya Kalua; Mochamad Agung Wibowo; Luther Alexander Latumakulita (PT. GWEX NET PUBLISHER, 2026)
Digital Twin (DT) technology is rapidly expanding from its manufacturing origins into smart tourism and national park management. However, its conceptual integration from an Information Systems (IS) perspective remains fragmented, leading to a lack of cohesive governance frameworks. This study conducts a bibliometric analysis of 412 academic documents extracted from the Scopus database (2005–2026) using the PRISMA framework and visualization tools such as VOSviewer and Biblioshiny. Our findings identify a major paradigm shift from isolated technical simulations toward socio-technical ecosystem modeling, categorized into clusters centered on the metaverse, smart city sustainability, and cultural heritage preservation. Crucially, we identify a significant research gap: the absence of a holistic socio-technical framework for DT adoption in protected area governance. This paper contributes by bridging the gap between technical engineering and organizational management, proposing a targeted research agenda focused on data interoperability, stakeholder engagement, and real-time ecological monitoring. These findings provide a strategic roadmap for IS scholars and policymakers to leverage digital twin technology for balancing tourism growth with environmental sustainability.